Teaching poetry using Instagram: An international, interdisciplinary study with adolescents mobilizing literacy and the arts - Lemieux, Amélie; Barton, Georgina; Lewkowich, David; White, Boyd; Ho, Stephanie (Language and Literacy / Langue et littératie, 2024)
Young people engage daily with various social media platforms to communicate with one another across the globe. Adolescents not only share text, but also use images and sound to express themselves on platforms such as Instagram and TikTok to provide access to user-created content. The recent emergence of InstaPoetry—poetry with images on Instagram—has been part of such communication and provides an entry point into adolescents’ engagement with literature and the arts. Limited research exists, however, on how this literacy practice, paired with virtual and in-person museum visits, influences young people’s self-expression. In addition, there is little known about how teachers can incorporate these literacy practices in the classroom. In this article, we offer ways of integrating and involving these dynamic dimensions into research projects based on four sites of inquiry located in Canada and Australia. Funded by the Social Sciences and Humanities Research Council of Canada, this research project provides concrete teaching to foster adolescents’ engagement with literature and the arts (i.e., contextual design, procedures, environment) in post COVID-19 times.